Development of CSE-UCLA evaluation model modified by using weighted product in order to optimize digital library services in higher education of computer in Bali - Dewa Gede Hendra Divayana; Agus Adiarta; Ida Bagus Gede Surya Abadi (Jurnal Pendidikan Vokasi, 2017)
This study aimed to obtain the draft of CSE-UCLA (Center for the Study of Evaluation- University of California in Los Angeles) evaluation model which is capable of measuring the level of optimization of digital library services, especially on higher education of computers in Bali. The method used in this research is the methods of research and development, the design of development is Walter Borg and Gall Meredith model. The overall study was conducted over three years, where research in the first year, especially up to design of the evaluation model is carried out for 3 months involving 2 education experts and 2 experts on informatics as research subjects in early trials that tested the design of the evaluation model and the accuracy calculation of the weighted product concept. The results of this study in the first year obtained a draft CSE-UCLA evaluation model modified using Weighted Product so as to measure the level of optimization of digital library services.